Histological identification of muscular sarcocystis: A report of two cases - Mani Makhija (Wolters Kluwer Medknow Publications, 2012)
Sarcocystis is an apicomplexan protozoan belonging to same phylum as toxoplasma. The parasite encysts inside striated muscles of its intermediate host. Humans are accidental host infected by eating food or water contaminated with oocysts or sporocysts of an infected definitive host. The infection is increasing in Southeast Asia and may be overlooked in histological sections if one is not aware of the histomorphological features. The size and shape of the bradyzoites and the appearance of the cyst wall are the reliable features to distinguish this parasite from other parasites of the same phylum. The incidence of human infection is rising in Southeast Asia and histopathology is an important method for the diagnosis of muscular infection. It is important to recognize the histomorphology of this parasite and its differentiation from similar parasites.